A method for characterizing the thermal stability and antimicrobial binding to Lipopolysaccharides of Gram-negative isogenic mutant strains - Navarro, Belén; Alarcón, Mackarenna; Osees, Maricarmen; Gómez Alvear, Felipe.; Sepúlveda, Romina V.; Huerta, Jaime; Opazo Delgado, María Cecilia.; Aguayo, Daniel (My University, 2021)
Isothermal Titration Calorimetry (ITC) is widely employed to assess antimicrobial affinity for lipopolysaccharide (LPS); nevertheless, experiments are usually limited to commercially available-LPS chemotypes. Herein we show a method that uses Differential Scanning Calorimetry (DSC) to characterize homogeneity artificial vesicles of LPS (LPS-V) extracted from isogenic mutant bacterial strains before analyzing the antimicrobial binding by ITC. This method allows us to characterize the differences in the Polymyxin-B binding and gel to crystalline liquid (β↔α) phase profiles of LPS-V made of LPS extracted from Escherichia coli isogenic mutant strains for the LPS biosynthesis pathway, allowing us to obtain the comparable data required for new antimicrobial discovery. A method for:•Obtaining LPS vesicles from isogenic mutant bacterial strains.•Characterize artificial LPS vesicles homogeneity.•Characterize antimicrobial binding to LPS
Keywords: Antimicrobial binding; Differential Scanning Calorimetry (ITC); Isothermal Titration Calorimetry (ITC); Lipopolysaccharides